Choice experiments in developing countries implementation, challenges and policy implications - Bennett, Jeff, 1954-; Birol, Ekin.; Edward Elgar Publishing (Cheltenham, Glos, U.K. ; Northampton, Mass. : Edward Elgar, 2010)
Choice Experiments in Developing Countries is an invaluable one-stop presentation of the best-practice case studies implementing the choice experiment method in developing countries. It highlights the theoretical and practical issues that should be taken into consideration when applying this method in a developing country context.
pt. I. Using choice experiments to investigate environmental conservation and economic development trade-offs -- pt. II. Using choice experiments to investigate environmental conservation and economic development trade-offs : the case of china's sloping land conversion programme -- pt. III. Using choice experiments to estimate developing countries' valuation of unique ecosystems -- pt. IV. Using choice experiments to inform effective and efficient provision of public and private goods and services -- pt. V. Using choice experiments to inform the agricultural sector and food industry.
Includes bibliographical references and index.
Keywords: Policy sciences; Developing countries -- Politics and government; Electronic books